PENGEMBANGAN MEDIA PEMBELAJARAN SPINNER BULAN UNTUK PESERTA DIDIK KELAS I SEKOLAH DASAR - Shirly Rizki Kusumaningrum (Al-Mudarris: Journal Of Education, 2024)
This research aims to develop a "Month Spinner" educational media for first-grade elementary students focusing on learning time in a yearly context. The ADDIE method was employed, encompassing analysis, design, development, implementation, and evaluation. Data was gathered through interviews, observations, and questionnaires from experts and users. The research findings indicate that this media is highly feasible and practical, with media expert validation at 98%, material expert validation at 89%, practicality tests by teachers at 93%, and students at 96%. This media is suitable for early grade learning, aiding comprehension of monthly sequences in a year.